Emerging chemotherapy-based treatments in anaplastic thyroid cancer: an updated analysis of prospective studies - Wang, Bi-Cheng; Lin, Guo-He; Kuang, Bo-Hua; Cao, Ru-Bo (Frontiers in Endocrinology, 2024)
Background For patients with anaplastic thyroid cancer (ATC) without mutational driver genes, chemotherapy is suggested to be the first-line treatment option. However, the benefits of chemotherapy in treating ATC are limited. In this analysis, we collected the prospective data reported since 2010 to analyze the emerging chemotherapy-based treatments in ATC comprehensively. Methods For this updated analysis, we searched PubMed (MEDLINE), Web of Science, Embase, and Cochrane CENTRAL databases from 1 January 2010 to 7 February 2024 for prospective clinical studies that contained chemotherapy-based treatments. This analysis was done to pool overall survival (OS), progression-free survival (PFS), objective response rates (ORRs), disease control rates (DCRs), and grade 3 or worse treatment-related adverse events (TRAEs). Results Six prospective clinical trials with 232 patients were included. Chemotherapy was commonly combined with targeted therapy or radiotherapy. The pooled median OS was 6.0 months (95% CI 4.1–9.7), and the median PFS was 3.2 months (95% CI 1.9–6.0) in patients with ATC who received chemotherapy-based strategies. The integrated ORR and DCR were 21% (95% CI 15%–27%) and 64% (95% CI 55%–72%), respectively. Regarding the grade 3 or worse TRAE, the pooled incidence was 68% (95% CI 47%–86%). Conclusion Although the emerging chemotherapy-based treatments showed antitumor activity in patients with ATC, these strategies failed to prolong the survival time substantially. More practical, safe, and novel therapeutic regimens for patients with ATC warrant further investigations.